HAAO rs3816183 Polymorphisms [T] Increase Anterior/Middle Hypospadias Risk in Southern Han Chinese Population - Liu, Yanqing; Fu, Wen; Fu, Kai; Zuo, Xiaoyu; Jia, Wei; Wang, Ning; Zhang, Yan; Liu, Guochang; Deng, Fuming (Frontiers in Pediatrics, 2022)
Hypospadias is one of the most common congenital external genital malformations, which is characterized by abnormal urethral meatus. However, the etiology remains to be incompletely understood. HAAO is a gene that encodes a protein, which catalyzes the synthesis of quinolinic acid, and has been identified as a risk gene for hypospadias. Thus, this study was conducted to elaborate the association between HAAO gene polymorphism rs3816183 T>C and hypospadias in the largest hypospadias cohort from Asia, including 577 patients and 654 healthy controls in China. The strength of interrelation was evaluated using 95% confidence intervals (CIs) and odds ratios (ORs). Based on the stratified analysis of hypospadias subtypes, it was found that the HAAO risk allele rs386183[T] enhances the susceptibility for hypospadias among patients with anterior/middle hypospadias subtypes (adjusted OR = 1.31, 95% CI = 1.05–1.64, p = 0.017). Enhanced risk of hypospadias in the entirety could not be demonstrated (OR = 1.20, 95% CI = 1.00–1.47, p = 0.054). In summary, our study found that the rs3816183[T] polymorphism is associated with increased risk of anterior/middle hypospadias among Southern Han Chinese children. The mechanisms by which the variations in the HAAO gene require further research.